Gallstone disease and the risk of cardiac mortality in patients with acute coronary syndrome - Su, Wen; Zhu, Jie-Gao; Li, Wei-Ping; Chen, Hui; Li, Hong-Wei (Frontiers in Cardiovascular Medicine, 2022)
Background: Gallstone disease is one of the most common gastrointestinal disorders, which has previously been reported to be associated with the incidence of cardiovascular disease. We aimed to investigate the association between gallstone disease and long-term outcomes in patients with acute coronary syndrome (ACS). Methods: A total of consecutive 13975 ACS patients were included in this analysis. Gallstone disease in our study included both gallstones and cholecystectomy. The primary endpoint was cardiac mortality. The secondary outcome was all-cause mortality. Relative risks were estimated using Cox proportional hazards regression. Results: During a median follow-up period of 2.96 years, 518 (4.2%) patients without gallstone disease and 62 (3.6%) patients in those with gallstone disease suffered cardiac death. After multivariable adjustment for established risk factors, subjects with gallstone disease had decreased risks of both cardiac mortality and all-cause mortality (HR=0.72, 95%CI: 0.55-0.95 and HR=0.75, 95%CI: 0.62-0.90, respectively). In patients with performed cholecystectomy, the associations between gallstones and risks for cardiac mortality and all-cause mortality turned out to be non-significant. HRs varied across subgroups depending on the presence of selected established risk factors. Conclusions: Presence of gallstone disease was associated with a significantly decreased risk of follow-up mortality in patients with ACS.